2015
DOI: 10.1161/hypertensionaha.115.05515
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Functional Evidence Supports LPAR1 as a Susceptibility Gene for Hypertension

Abstract: Abstract-Essential hypertension is a complex disease affected by genetic and environmental factors and serves as a major risk factor for cardiovascular diseases. Serum lysophosphatidic acid correlates with an elevated blood pressure in rats, and lysophosphatidic acid interacts with 6 subtypes of receptors. In this study, we assessed the genetic association of lysophosphatidic acid receptors with essential hypertension by genotyping 28 single-nucleotide polymorphisms from genes encoding for lysophosphatidic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Both in vitro and in vivo data suggested that LPA We found that the expression of ATX and LPAR1 in the renal cortex of db/db mice was increased compared with wildtype mice, and that ki16425 treatment reduced glomerular injury, which suggested that LPAR1 signaling was involved in the pathogenesis of diabetic nephropathy. It was previously reported that the expression of LPAR1 was increased in white blood cells of patients with essential hypertension, 37 which is a major factor for kidney injury during diabetes progression. 1,3,4 These results indicated that LPAR1 expression was correlated with kidney injury.…”
Section: Discussionmentioning
confidence: 98%
“…Both in vitro and in vivo data suggested that LPA We found that the expression of ATX and LPAR1 in the renal cortex of db/db mice was increased compared with wildtype mice, and that ki16425 treatment reduced glomerular injury, which suggested that LPAR1 signaling was involved in the pathogenesis of diabetic nephropathy. It was previously reported that the expression of LPAR1 was increased in white blood cells of patients with essential hypertension, 37 which is a major factor for kidney injury during diabetes progression. 1,3,4 These results indicated that LPAR1 expression was correlated with kidney injury.…”
Section: Discussionmentioning
confidence: 98%
“…In humans, polymorphism in the LPA1 receptor has been related to augmented risk of essential hypertension. Given that stress, the main environmental cause of depression, increases the susceptibility of patients with risk alleles, 69 genetic variants in this receptor may participate in the aetiology of depression. Here, we have identified for we believe the first time the possible relationship of the LPA1 receptor with a mixed depressive-anxiety phenotype, shedding light on the unknown neurobiological basis of this subtype of depression 5 and generating the opportunity to explore a new therapeutic target for the treatment of mood disorders, namely the anxious-depression subtype.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is believed to be one of the most common comorbidities associated with chronic renal disease (Lash et al, 2009 ), obesity and type 2 diabetes (Landsberg and Molitch, 2004 ; Kotchen, 2010 ). Presently, genome-wide association studies (GWAS) have identified a series of genetic loci and pathways associated with blood pressure (Xu et al, 2015 ; Liu et al, 2016 ). The environmental factors, such as, dietary salt intake, alcohol consumption and lack of exercise, are also linked to the occurrence of hypertension (Fuchs et al, 2001 ; Karppanen and Mervaala, 2006 ).…”
Section: Introductionmentioning
confidence: 99%